Torrefaction and pelletization of oil palm waste and forestry residue - Nur Nabihah, Ramli (2017)
This study describes the effect of torrefaction on the characteristics of pellet formed from palm kernel shell (PKS) and Kulim sawdust as a potential of solid fuel.. The characteristics of pellet formed such as density and strength at different torrefaction temperatures and at different biomass particle sizes which at the range between 0.5 to 4.0 mm were examined. The samples were torrefied at different temperatures which were 240°C, 270°C and 300°C for 30 minutes. The calorific value of raw and torrefied biomass were measured before and after treatment. The sample was then densified into pellets through hot press machine at 130°C and 12 MPa for about 10 minutes. The pellet was analysed through Scanning Electron Microscope (SEM) and compression strength of pellet analysis. SEM analysis is to study the surface morphology of EFB and PKS pellets before and after torrefaction process. Compression test is to study the strength of pellet by identifying the force required to break the pellet. The highest calorific value of PKS and Kulim is at torrefaction temperature of 300°C. The expected energy yield for those biomass samples ranges from 89.0% to 100%. Calorific value of the pellets is directly proportional to the torrefaction temperature. Higher heating temperature results the decrease of mass due to thermal decomposition of the hemicellulose part of biomass. High temperature makes pellets more brittle and breakable pellets due to the uneven surface of biomass as the structure changes with temperature throughout the torrefaction.